Knowledge, beliefs, and behaviors related to secondhand smoke and smoking in the home: a qualitative study with men in Malaysia - Abdul Mutalib, Raisya Nur Syazmeen; Abd Rani, Nurul Latiffah; Zulkifli, Aziemah; Abd Latif, Norul Hernani; Dobson, Ruaraidh; Engku Ibrahim, Tengku Azmina; Semple, Sean; Zainal Abidin, Emilia; Uny, Isabelle; O’donnell, Rachel (Oxford University Press, 2022)
Introduction: Despite the health risks associated with secondhand smoke (SHS) exposure, smoking in the home is common in Malaysia, and almost exclusively a male behavior. Aims and Methods: This study explored male smokers’ knowledge, beliefs, and behaviors related to SHS exposure and smoking in the home, to guide future intervention development. Twenty-four men who smoked and lived in Klang Valley, Kuantan, or Kuala Terengganu took part in semi-structured interviews which explored knowledge and beliefs regarding SHS in the home, and associated home-smoking behaviors. Data were managed and analyzed using the framework approach. Results: There was limited knowledge regarding the health risks associated with SHS: the smell of SHS in the home was a more prominent concern in most cases. Many had no rules in place restricting home smoking, and some suggested that smoking in specific rooms and/or near windows meant SHS was not “shared” with other household members. A few fathers had created but not maintained a smoke-free home prior to and/or after their children were born. Desire to smoke in the home conflicted with men’s sense of responsibility as the head of the household to protect others and set a good example for their children. Conclusions: Men’s home-smoking behaviors are shaped by a lack of understanding of the health risks associated with SHS exposure. Gaining a broader understanding of the factors that shape men’s decisions to create a smoke-free home is important to facilitate the development of culturally appropriate interventions that address their responsibility to protect other household members from SHS exposure. Implications: Our findings highlight the need for public information campaigns in Malaysia to educate men who smoke regarding the health harms associated with SHS in the home and the ways in which SHS travels and lingers in household air. This is important given men’s concerns about SHS often focus on the smell of cigarette smoke in the home. Our findings suggest a number of potential avenues for future intervention development, including household and community-level initiatives that could build on men’s sense of responsibility as the head of the household and/or their general desire to protect their families.